Implementing Mistake Buster Technique to Improve the Students` Grammar Mastery - Nurbaiti, Nurbaiti; Maghdalena, Jeane; Sofyan, Dedi (UNIB Press, 2023)
Abstract This research aimed to investigate the effectiveness of the Mistake Buster technique in improving the students` grammar mastery at seven grade students of junior high school number 11 of Bengkulu City. Collaborative classroom action research was carried out and it had two cycles designed with four steps; Planning, implementing, observing, and reflecting on the action. The subjects of this research consisted of 32 students. The instruments were a test, observation checklist, and field note. The result showed that there was an improvement in students` grammar mastery by applying the Mistake Buster technique in the grammar teaching. It seemed that the Mistake Buster technique is quite effective to help the students` grammar mastery, to encourage students` motivation, and to build an active learning atmosphere in the EFL teaching and learning process. Moreover, the result provides teachers with more insight and reference regarding to the technique in teaching English grammar and applying it to their teaching process.